2011
DOI: 10.3109/17477166.2010.518241
|View full text |Cite
|
Sign up to set email alerts
|

Body size and growth from birth to 2 years and risk of overweight at 7–9 years

Abstract: This study showed the simultaneous association of large infant size at 1 year and early rapid infant growth along with overweight at 7-9 years, as well as involvement of early growth velocity variations. Early infancy, a phase of very rapid growth, constitutes a critical period for the onset of overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…It could be argued that if the outcome would be more clinically based, such as long-term consequences of macrosomia, then growth velocity rather than size would have better performance. Indeed, in infants it has consistently been shown that growth velocity in early infancy is more predicting of subsequent obesity than any crosssectional measurement [33].…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that if the outcome would be more clinically based, such as long-term consequences of macrosomia, then growth velocity rather than size would have better performance. Indeed, in infants it has consistently been shown that growth velocity in early infancy is more predicting of subsequent obesity than any crosssectional measurement [33].…”
Section: Discussionmentioning
confidence: 99%
“…These results are of special relevance considering the reported Early protein intake, weight gain and body fat J Escribano et al association of weight gain during the first 2 years of life with later overweight or obesity risk (at 7 --9 years), 32 suggesting that rapid weight gain early in life is a key determinant factor for childhood obesity. 33 FM at 6 months predicted later BMI at 12 and 24 months in this study.…”
Section: Discussionmentioning
confidence: 85%
“…In a recent study, BMI and body weight attained at 1 y of life were shown to have predictive power for the development and persistence of overweight during childhood (40). Furthermore, cellular studies on human body fat suggested that it expands rapidly during the first year of life predominantly by increasing the adipocyte size that subsequently decreases for 1 or 2 y and remains stable for several years (41,42).…”
Section: Discussionmentioning
confidence: 97%